Impacts of Covid-19 on tuberculosis: an integrative review - Braga, Rebeca Sousa; Ferreira, Melisane Regina Lima; Orfão, Nathalia Halax (O Mundo da Saúde, 2024)
The objective of this review was to identify and describe how the Covid-19 pandemic affected tuberculosis (TB) prevention and care actions within Primary Health Care (PHC). This is an integrative literature review conducted through the databases Embase, MEDLINE, Scopus, Web of Science, and LILACS. Primary studies available in full, published between 2020 and 2023 in English, Portuguese, or Spanish, were considered. Review articles and publications belonging to the grey literature were excluded. The database search identified 339 publications. After meeting the previously established criteria, eleven articles were selected for full reading and analysis. It was found that the onset of the Covid-19 pandemic directly interfered with the goals and achievements obtained over the past decades in the fight against TB, in addition to increasing the vulnerabilities in TB prevention and care actions within PHC due to the scarcity of human and material resources that were redirected to meet the demands of Covid-19, which directly impacted unfavorable treatment outcomes for the disease. These results highlight the importance of reassessing strategies and implementing public policies that strengthen the response to TB control, while also pointing to the need for new studies on the changes in the epidemiological profile of the disease during the pandemic, as well as analyzing the strategies adopted by health services to ensure the continuity of TB care during this period.